2020
DOI: 10.5194/acp-2020-1208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of Los Angeles basin pollution and stratospheric intrusions on the surrounding San Gabriel Mountains as seen by surface measurements, lidar, and numerical models

Abstract: Abstract. In this work, the impact of Los Angeles basin pollution transport and stratospheric intrusions on the surface ozone levels observed in the San Gabriel Mountains is investigated based on a combination of surface and lidar measurements as well as WRF-Chem (Weather Research and Forecasting with Chemistry) and WACCM (Whole Atmosphere Community Climate Model) model runs. The number of days with observed surface ozone levels exceeding the National Ambient Air Quality Standards exhibit a clear seasonal patt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Up to an altitude of about 20 km, ozonesondes constitute the most important data source with long-term coverage for the derivation of ozone trends. UAV-borne ozone observations have been reported in the literature for close-to-the-ground (boundary layer) deployment using Electrochemical Concentration Cell (ECC) ozonesondes (by Illingworth et al [7]; Chouza et al [82]). Gronoff et al [83] reported UAV-ozone measurements from ship plume emissions using an octocopter with a 2B-Technologies POM ozone sensor, which calculates ozone concentration from optical absorption of UV light generated from a low-pressure mercury lamp.…”
Section: Ozone Profiling Over Cyprusmentioning
confidence: 99%
“…Up to an altitude of about 20 km, ozonesondes constitute the most important data source with long-term coverage for the derivation of ozone trends. UAV-borne ozone observations have been reported in the literature for close-to-the-ground (boundary layer) deployment using Electrochemical Concentration Cell (ECC) ozonesondes (by Illingworth et al [7]; Chouza et al [82]). Gronoff et al [83] reported UAV-ozone measurements from ship plume emissions using an octocopter with a 2B-Technologies POM ozone sensor, which calculates ozone concentration from optical absorption of UV light generated from a low-pressure mercury lamp.…”
Section: Ozone Profiling Over Cyprusmentioning
confidence: 99%
“…Recently, we supported the NASA Fire Influence on Regional to Global Environments Experiment-Air Quality (FIREX-AQ) campaign in the summer of 2019. Third, we generated the vertical distributions of ozone and aerosol information at NASA Tropospheric Ozone Lidar Network (TOLNET) sites so that transient events, e.g., stratospheric intrusions and transport of polluted air from the urban area to the nearby mountains (e.g., from the Los Angeles basin to the San Gabriel mountains [6]), could be captured. Fourth, the NCAR system was aimed at providing long-term air quality simulations for use in health impact studies.…”
Section: Introductionmentioning
confidence: 99%